Konsep Pendidikan Karakter Islam: Relevansinya Terhadap Pendidikan Berkelanjutan SDG-4 (Pemikiran Sayyid Muhammad Bin Alwi Al-Maliki) - Ikrimatul Maslamah; Zulfatul Mufidah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study explores the concept of Islamic character education in the thought of Sayyid Muhammad bin Alwi al-Maliki and its relevance to Sustainable Development Goal (SDG) 4, which promotes inclusive, equitable, and quality education. The research aims to analyze how al-Maliki’s educational ideas—rooted in classical Islamic tradition—can contribute to addressing moral and character crises in contemporary education, particularly in the context of building sustainable and value-based education systems.Using a qualitative approach with a library research method, this study examines al-Maliki’s key works and supporting literature on Islamic education and global education policies. The analysis focuses on core values and educational strategies that he promotes to shape well-rounded individuals who are not only intellectually capable but also morally and spiritually grounded. Findings indicate that al-Maliki’s integration of ethical values and character formation aligns with the objectives of SDG 4, especially in fostering responsible, compassionate, and socially engaged learners. His educational philosophy offers a relevant framework for Islamic education systems seeking to elevate character development alongside academic goals. The study also underscores the potential of classical Islamic pedagogy to contribute meaningfully to global educational reform and sustainability discourses